Implementation of Android-Based English Application System as Learning Tool for 6-12 Years Old Due to Covid-19 - Roheli, R; Rahayu, Diah Afrianti; Marcha, Famela; Darmayanto, D (SAFE-Network, 2023)
Background based on science development today requires the education world to increase qualities in all fields. With technology existence in modern times, it is expected to be able to increase quality of learning more effectively. The purposes of conducting this study are (1) bringing students into a new teaching and learning atmosphere so that they do not get bored easily in learning during the covid-19 pandemic, (2) teachers can monitor students’ development who are less motivated by the learning provided by the teacher through assignments such as only through WhatsApp or Google Classroom, (3) developing learning application in schools. In the English learning application, there are 15 English vocabulary lessons about colors, numbers, fruits, letters, and others accompanied by exercises and evaluations to measure students' understanding and make them able to learn independently, also as an alternative learning media. This application is supported by images, sounds and animations to attract students' learning interest. Data collection methods were tests, observations and documentation. The subjects of this study were 50 students. Various instruments were used to collect data such as: (1) students’ response questionnaires (2) interview to support the results of students’ response questionnaires (3) learning evaluation questions through android application media.